Effectiveness of Realistic Mathematics Education Assisted by Interactive Videos on Students’ Learning Outcomes and Motivation - Asyari, Lutfi; Anugrah, Yova; Kusumaryono, Suyato; Sumartini, Tina Sri (Department of Mathematics Education Program IPI Garut, 2025)
Salah satu pendekatan efektif untuk menjembatani konsep matematika abstrak dengan situasi kehidupan nyata adalah Realistic Mathematics Education (RME). Penelitian ini bertujuan mengkaji efektivitas model pembelajaran RME berbantuan video interaktif dalam meningkatkan motivasi dan hasil belajar matematika siswa kelas V salah satu SDN di Garut. Metode penelitian menggunakan pendekatan kuantitatif dengan Quasi Experimental dan Non-Equivalent Control Group Design. Subjek penelitian meliputi 60 siswa yang dibagi menjadi kelas eksperimen dan kelas kontrol. Data dikumpulkan melalui tes tulis. Analisis data dilakukan dengan statistika deskriptif dan uji t. Sebelum penerapan, motivasi belajar siswa di kelas eksperimen sebesar 54,9%, meningkat menjadi 81,1% setelah perlakuan. Rata-rata hasil belajar meningkat dari 69,73 menjadi 87,00 pada kelas eksperimen, sedangkan pada kelas kontrol hanya naik dari 69,67 menjadi 74,60. Hasil ini menunjukkan penerapan RME berbantuan video interaktif berpengaruh terhadap peningkatan motivasi dan hasil belajar siswa. Penelitian merekomendasikan pemanfaatan teknologi pembelajaran untuk menciptakan pembelajaran yang lebih menarik, interaktif, dan efektif. One effective approach to bridge abstract mathematical concepts with real-life situations is Realistic Mathematics Education (RME). This study aims to examine the effectiveness of the RME model assisted by interactive videos in improving the motivation and mathematics learning outcomes of fifth-grade students at one of SDN in Garut. The research employed a quantitative approach with a Quasi-Experimental design and a Non-Equivalent Control Group Design. The subjects consisted of 60 students, divided into an experimental class and a control class. Data were collected through written tests and analyzed statistically using descriptive statistics and Independent Sample T-Test. Prior to implementation, students’ learning motivation in the experimental class was 54.9%, which increased to 81.1% after the treatment. The average learning outcomes improved from 69.73 to 87.00 in the experimental class, while the control class increased only from 69.67 to 74.60. These results indicate that the implementation of RME assisted by interactive videos has a significant effect on enhancing students’ motivation and learning outcomes. The study recommends utilizing educational technology to create more engaging, interactive, and effective learning experiences.